2021
DOI: 10.4236/ojbm.2021.94105
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Effects of Influencing Factors of International Students on Employability: A Case Study in China

Abstract: The current study explored the effects of international students' influencing factors on their perceived employability: A case study of China. The explanatory research design was adopted to involve 514 international African students in the study. The research was conducted with a random sampling technique. Fifty (50)-test items standardized questionnaire was adopted as research instrument for the study. Using Structural Equation Modeling (SEM), the study found that there is a strong positive relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Since enough data points were available, PLS-SEM was used to evaluate the innovativeness of small and medium-sized enterprises in Jiangsu. PLS covers structural and measurement models and the evaluation of internal model validity and dependability (Kir et al, 2021; Owusu et al, 2022). In the past three decades, PLS has grown in importance in business research (Hair, Ringle, & Sarstedt, 2012).…”
Section: Main Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since enough data points were available, PLS-SEM was used to evaluate the innovativeness of small and medium-sized enterprises in Jiangsu. PLS covers structural and measurement models and the evaluation of internal model validity and dependability (Kir et al, 2021; Owusu et al, 2022). In the past three decades, PLS has grown in importance in business research (Hair, Ringle, & Sarstedt, 2012).…”
Section: Main Results and Discussionmentioning
confidence: 99%
“…By examining the interactions between the environment, the economy, and sustainable development, this study intends to give insight on the complexities of achieving environmental sustainability in key sectors (Ahakwa et al, 2023; Ahmed et al, 2022; Xu & Li, 2020). Prior studies have demonstrated that this sampling methodology is accurate and provides reliable outcomes (Cobbinah et al, 2020; Kir et al, 2021; Owusu et al, 2022; Sappor et al, 2023; F. A. Sarpong et al, 2022, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model's "fitness" to the data is estimated to determine whether was deemed appropriate to measure the relationship that exist between the dependent and independent variables. Model fit evaluation is used to verify a theoretical model via parameter fitting (Benah & Li, 2020;Kir et al, 2021). The model's fitness was assessed using the RMSEA, CFI, TLI, GFI, NFI, and Standardized Root Mean Square Residual indices (SRMR).…”
Section: Resultsmentioning
confidence: 99%